City Through the Eyes Of Students' Youth: Assessment and Regional Practices (A Case Study of Nizhny Novgorod) - O. R. Chepyuk; O. Yu. Angelova; S. D. Makarova; N. G. Bryandinskaya; O. V. Petrova (Высшее образование в России)
Russian universities at the present stage play a significant role in shaping the students professional preferences and migration expectations, thereby contributing to socio-economic development and influencing the process of human capital management at the regional level. The issue of immersing a university in the problems of a city (region) becomes especially relevant in light of global challenges, such as demographic changes, economic instability, and a lack of qualified personnel. One of the important areas of research is the analysis of how students evaluate the city of study, which may become their future place of residence and professional activity. The publication presents the results of such a study – a long-term survey of young people (students of the largest Nizhny Novgorod university – Lobachevsky University) about the conditions for their professional growth and development in one of the largest Russian cities – Nizhny Novgorod. The survey period (2017-2023) covered not only significant events related to the implementation of large infrastructure projects in the city (2018 FIFA World Cup, the 800th anniversary of Nizhny Novgorod in 2021, recognition of the city as New Year’s (2022) and Youth (2023) capitals of Russia), but also during the COVID-19 pandemic. One of the areas of the research that determined its novelty was the assessment of the city as a center for the development of creative industries, as well as a structural analysis of the results when dividing respondents by type of planned career trajectories. The discussion compared the results with similar studies from other regions of Russia. The results of the study are of interest for university management and regional policy, emphasizing the importance of the interaction of educational institutions with the urban environment in the context of the preservation and development of human resources in the region.